A nanofiltration membrane for high temperature feed liquid separation and a method for preparing the same
Patent Information
- Application Number
- CN202611080925.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-07-21
AI Technical Summary
[0006]本发明的目的是提供一种用于高温料液分离的纳滤膜及其制备方法,旨在解决现有纳滤膜在高温工况下通量衰减严重、高价阴离子盐截留率显著下降以及长期运行稳定性不足的问题,使所述纳滤膜在高温条件下仍能保持优异的分离性能和结构完整性,满足工业高温料液处理的实际应用需求
本发明所提供的纳滤膜通过在磺化聚醚醚酮支撑层与含氟聚酰胺分离层之间引入氨基化埃洛石纳米管中间层,使三层结构之间通过氢键作用和共价键作用形成了牢固的界面结合,有效抑制了高温运行条件下层间热膨胀失配导致的界面剥离和结构损伤,从而显著提高了膜在高温工况下的结构完整性和长期运行稳定性。含氟聚酰胺分离层中刚性联苯结构和三氟甲基侧基的引入,使分离层在高温下能够维持致密的交联网络,避免了常规聚酰胺层因链段热运动加剧而导致的截留性能劣化。磺化聚醚醚酮支撑层与中间层和分离层形成了良好的热膨胀梯度匹配。上述技术方案使纳滤膜能够在高温料液中直接进行分离处理,省去了料液降温环节所需的换热设备和能耗,同时膜表面较低的污染物附着倾向也有利于维持长期运行的稳定性,对于推动纳滤技术在高温物料处理领域的实际应用具有积极意义。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanofiltration membrane technology, specifically relating to a nanofiltration membrane for high-temperature liquid-feed separation and its preparation method. Background Technology
[0002] Nanofiltration membranes, as a pressure-driven membrane separation technology between ultrafiltration and reverse osmosis, have been widely used in water softening, industrial wastewater treatment, and material concentration and separation due to their high rejection rate for divalent and multivalent ions and relatively low operating pressure. In industrial processes such as chemical, printing and dyeing, pharmaceutical, food processing, and coal chemical industries, a large amount of the feed liquid itself has high-temperature characteristics. If nanofiltration separation can be performed directly on the high-temperature feed liquid, it can not only eliminate the need for heat exchange equipment and energy consumption for cooling the feed liquid, but also effectively inhibit microbial growth and increase membrane flux, thereby significantly reducing treatment costs and improving process efficiency. However, existing commercial nanofiltration membranes are difficult to meet the separation requirements of high-temperature conditions in practical applications.
[0003] Currently, most mainstream nanofiltration membrane products on the market are aromatic polyamide composite nanofiltration membranes, which are composed of a non-woven fabric support layer, a porous intermediate layer, and a polyamide separation layer through interfacial polymerization. The polyamide separation layer endows the membrane with excellent salt retention performance, but this type of material is extremely sensitive to temperature. Wu Haijie et al., in their article "Industrial High-Salinity Wastewater Treatment Method Based on Nanofiltration Membrane Separation Technology," demonstrated that, under otherwise constant operating conditions, the desalination rate and retention rate of the nanofiltration membrane gradually decrease with increasing temperature, and the decrease in retention rate is more significant. The deterioration of separation performance is not a simple reversible change; membrane structural damage caused by high temperature is often irreversible and difficult to fully recover even after cooling.
[0004] In recent years, researchers have explored various approaches to address the insufficient thermal stability of nanofiltration membranes. Some scholars have attempted to enhance thermal stability by increasing the interfacial polymerization temperature to form a thicker and denser separation layer; others have enhanced its high-temperature resistance by adding fluorine-containing monomers to the aqueous phase to increase the glass transition temperature of the polyamide desalination layer. Wang Chun et al., in their paper "Preparation and High-Temperature Nanofiltration Performance of Para-Aromatic Polyamide Composite Nanofiltration Membranes," prepared PPTA / PA composite nanofiltration membranes using para-aromatic polyamide ultrafiltration membranes as the base membrane via interfacial polymerization and studied their nanofiltration performance at high temperatures. Zi-Lu Zhang et al., in their paper "Thermally Stable Thin-Film Composite Nanofiltration Membranes Derived from 3,3′-Diaminobenzidine," used 3,3′-diaminobenzidine as the aqueous phase monomer and enhanced the rigidity of the crosslinked network by introducing rigid structural units into the polyamide network. The prepared nanofiltration membrane maintained a stable sodium sulfate rejection rate of 97.0% within the temperature range of 25–85℃. While the aforementioned studies have made some progress in improving the thermal stability of nanofiltration membranes, most of them are still in the laboratory research stage. The reported water flux levels of the membranes at high temperatures are generally low, and the long-term operational stability has not been fully verified. Furthermore, the preparation process is complex and difficult to scale up, and there is still a significant gap between them and the actual application requirements of high-temperature liquid treatment in industry.
[0005] Therefore, there is an urgent need for a nanofiltration membrane and its preparation method that can operate stably for a long time under high temperature conditions, has excellent retention performance for high-valence anionic salts, has a low water flux decay rate, and whose preparation process is suitable for industrial production. Summary of the Invention
[0006] The purpose of this invention is to provide a nanofiltration membrane for high-temperature liquid separation and its preparation method, aiming to solve the problems of severe flux decline, significant decrease in high-valence anion salt rejection rate, and insufficient long-term operational stability of existing nanofiltration membranes under high-temperature conditions, so that the nanofiltration membrane can still maintain excellent separation performance and structural integrity under high-temperature conditions, and meet the practical application needs of industrial high-temperature liquid treatment.
[0007] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of this invention provides a nanofiltration membrane for high-temperature liquid-feed separation, the nanofiltration membrane having a four-layer composite structure, comprising, from bottom to top: Non-woven fabric reinforcement layer; A sulfonated polyether ether ketone porous support layer is disposed on the upper surface of the nonwoven fabric reinforcement layer; An aminated halloysite nanotube intermediate layer is disposed on the upper surface of the sulfonated polyether ether ketone porous support layer; A fluorinated polyamide separation layer is disposed on the upper surface of the intermediate layer of the aminated halloysite nanotubes. The fluorinated polyamide separation layer is formed by interfacial polymerization of a fluorinated aromatic diamine monomer and a polyacrylamide monomer.
[0008] Furthermore, the nonwoven reinforcement layer is polyethylene terephthalate nonwoven fabric or polypropylene nonwoven fabric.
[0009] Furthermore, the degree of sulfonation of the sulfonated polyether ether ketone is 45% to 65%.
[0010] Furthermore, the preparation method of the sulfonated polyether ether ketone includes: dissolving polyether ether ketone in concentrated sulfuric acid, reacting at a temperature of 50-80°C for 4-12 hours, washing the reaction product with deionized water until neutral, and then drying it to obtain sulfonated polyether ether ketone.
[0011] The sulfonated polyetheretherketone (PEEK) porous support layer supports and anchors the upper intermediate and separation layers, while providing low-resistance transport channels for water molecules. The PEEK backbone contains numerous rigid aromatic rings and ether bonds, exhibiting high crystallinity, high melting temperature, and excellent resistance to thermal creep. Its high-temperature structural stability is significantly superior to that of conventional amorphous polysulfone and polyethersulfone materials. Under high-temperature feed conditions, the support layer pores are less prone to thermal softening, deformation, and creep collapse, providing a structurally and dimensionally stable substrate for the upper functional membrane layers, thus ensuring the high-temperature operational stability of the composite membrane from the bottom up. The introduction of sulfonic acid hydrophilic groups significantly enhances the surface hydrophilicity of the support layer. During phase transformation and membrane formation, it optimizes the membrane pore microstructure, facilitating the formation of highly porosity, highly interconnected finger-like channels, effectively reducing the resistance to water molecule transport across the membrane and increasing the pure water flux of the membrane. Meanwhile, the negatively charged sulfonic acid groups on the surface of the support layer pores can form an electrostatic repulsion environment inside the pores, effectively inhibiting the adsorption, accumulation and blockage of polyvalent anionic salts in the support layer pores under high-temperature conditions, avoiding rapid decay of membrane flux, and helping to improve the separation stability of the overall membrane module in long-term operation.
[0012] Furthermore, the preparation method of the aminated halloysite nanotubes includes: dispersing halloysite nanotubes in an organic solvent, adding a silane coupling agent, reacting at reflux temperature for 6 to 24 hours, and obtaining aminated halloysite nanotubes after washing and drying the reaction product.
[0013] Further, the silane coupling agent is 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane; the mass ratio of halloysite nanotubes to silane coupling agent is 1:0.05-0.5; the organic solvent is selected from at least one of toluene, anhydrous ethanol, isopropanol or N,N-dimethylformamide.
[0014] The aminated halloysite nanotube interlayer improves the interfacial bonding between the support layer and the separator layer, providing additional water transport channels. After grafting with a silane coupling agent, the interlayer exhibits amino groups on its surface. During interfacial polymerization, these amino groups undergo amidation with acyl chloride groups in the organic phase, covalently bonding the separator layer to the interlayer surface. Simultaneously, the silanol groups on the halloysite nanotube surface interact with the sulfonic acid groups of sulfonated polyether ether ketone in the support layer through hydrogen bonding. This enhances the interfacial bonding between the support layer, interlayer, and separator layer, reducing the likelihood of relative slippage or delamination between layers under high-temperature operating conditions. Furthermore, the hollow cavities of the halloysite nanotubes create numerous short-range nano-water transport pathways within the interlayer, effectively shortening the cross-layer mass transfer path of water molecules, offsetting the increased mass transfer resistance introduced by the interlayer membrane, and ensuring high water permeability of the composite membrane.
[0015] Further, the fluorinated aromatic diamine monomer is at least one of 2,2′-bis(trifluoromethyl)-4,4′-diaminobiphenyl, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, or 4,4′-(hexafluoroisopropylidene)diphenylamine; the polyacrylamide chloride monomer is at least one of pyromellitic tricarboxylic acid chloride, terephthaloyl chloride, or isophthaloyl chloride.
[0016] The fluorinated polyamide separation layer is formed by crosslinking a fluorinated aromatic diamine with a polyacrylamide via an interfacial polycondensation reaction. The fluorinated aromatic diamine monomer introduced into this layer contains biphenyl or diphenyl ether structures, whose rigidity restricts the thermal motion of the crosslinked polymer chains at high temperatures. This results in a smaller degree of pore size expansion in the separation layer as the temperature increases, which is the main structural reason why this separation layer can maintain a stable rejection rate over a wide temperature range. The fluorinated surface has low surface energy, making it less susceptible to adhesion of trace organic matter or colloidal particles in the feed solution. This crosslinked amide network preferentially permeates water molecules while exhibiting a high rejection rate for polyvalent anions. Combined with the electrostatic repulsion of charged groups on the membrane surface, it achieves effective separation of high-valent salts such as sodium sulfate.
[0017] A second aspect of the present invention provides a method for preparing the nanofiltration membrane for high-temperature liquid-feed separation, comprising the following steps: (1) Dissolve sulfonated polyether ether ketone in an organic solvent to prepare a film-forming solution, coat the film-forming solution on the surface of the nonwoven fabric reinforcement layer, and then immerse it in water for phase inversion to obtain a sulfonated polyether ether ketone porous support layer composite on the nonwoven fabric reinforcement layer. (2) Aminated halloysite nanotubes are dispersed in a liquid medium to form a dispersion, and the dispersion is coated on the surface of the sulfonated polyether ether ketone porous support layer. After drying, an aminated halloysite nanotube intermediate layer is formed. (3) An aqueous solution containing a fluorinated aromatic diamine monomer is applied to the surface of the intermediate layer of aminated halloysite nanotubes. After removing excess liquid from the surface, an organic solution containing a polyacrylamide monomer is applied to the same surface for interfacial polymerization. After the reaction is completed, the solution is heated to obtain a fluorinated polyamide separation layer, which is a nanofiltration membrane for high-temperature liquid-feed separation.
[0018] Further, in step (1), the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; the mass concentration of sulfonated polyether ether ketone in the film-forming solution is 15% to 20%; and the temperature of the water used for the phase inversion is 25 to 60°C.
[0019] Further, in step (2), the liquid medium is water or a mixture of ethanol and water; the mass concentration of aminated halloysite nanotubes in the dispersion is 0.05% to 0.5%; in step (3), the mass concentration of fluorinated aromatic diamine monomer in the aqueous phase solution is 1.0% to 3.0%; the mass concentration of polyacrylamide chloride monomer in the organic phase solution is 0.1% to 0.3%; the temperature of the interfacial polymerization reaction is 25 to 60°C, and the time is 1 to 5 minutes.
[0020] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: The nanofiltration membrane provided by this invention introduces an aminated halloysite nanotube interlayer between the sulfonated polyether ether ketone (PEEK) support layer and the fluorinated polyamide separation layer. This interlayer structure forms a strong interfacial bond through hydrogen bonding and covalent bonding, effectively suppressing interfacial delamination and structural damage caused by interlayer thermal expansion mismatch under high-temperature operating conditions. This significantly improves the membrane's structural integrity and long-term operational stability under high-temperature conditions. The introduction of rigid biphenyl structures and trifluoromethyl side groups in the fluorinated polyamide separation layer enables it to maintain a dense cross-linked network at high temperatures, avoiding the degradation of retention performance caused by increased thermal motion of chain segments in conventional polyamide layers. The sulfonated PEEK support layer forms a good thermal expansion gradient match with the interlayer and separation layer. This technical solution allows the nanofiltration membrane to directly separate materials in high-temperature solutions, eliminating the need for heat exchange equipment and energy consumption required for cooling the solution. Simultaneously, the low tendency for contaminant adhesion on the membrane surface also contributes to maintaining long-term operational stability. This has positive significance for promoting the practical application of nanofiltration technology in the field of high-temperature material processing. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Unless otherwise specified, all raw materials used in the embodiments are commercially available products. The following sources are illustrative examples.
[0023] Halloysite nanotubes were purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd., model XFI50; polyethylene terephthalate (PET) nonwoven fabric was purchased from Mingguan Purification Materials (Zhejiang) Co., Ltd., model MGPT-N120; polypropylene nonwoven fabric was purchased from Mingguan Purification Materials (Zhejiang) Co., Ltd., model MGPP-N120; and Matrimid 5218 polyimide was purchased from Zeshancheng New Materials (Wuhan) Co., Ltd. Example 1
[0024] This embodiment provides a nanofiltration membrane for high-temperature liquid-feed separation, the preparation method of which includes the following steps: (1) 10g of polyetheretherketone (PEEK) powder was dissolved in 200mL of 98% concentrated sulfuric acid and stirred at 70℃ for 8 hours. After the reaction was completed, the product was slowly poured into a large amount of deionized water to precipitate. The product was repeatedly washed with deionized water until the washing solution was neutral (pH≈7). The product was then vacuum dried at 60℃ for 24 hours to obtain sulfonated polyetheretherketone (SPEEK). The degree of sulfonation of the obtained SPEEK was determined to be 55% by acid-base titration.
[0025] 18g of SPEEK was dissolved in 82g of N,N-dimethylacetamide (DMAc) and stirred at 60°C for 12 hours. After standing to remove bubbles, a film-forming solution with a solid content of 18% was obtained. This film-forming solution was uniformly coated onto the upper surface of polyethylene terephthalate (PET) nonwoven fabric (120μm thick, 75% porosity) using a doctor blade with a doctor blade gap of 150μm. Immediately after coating, the entire nonwoven fabric and coating layer were immersed in a deionized water coagulation bath at 25°C for phase inversion molding for 10 minutes. After removal, the fabric was thoroughly washed with deionized water to obtain a SPEEK porous support layer composited on the nonwoven fabric.
[0026] (2) 5 g halloysite nanotubes were dispersed in 150 mL of anhydrous toluene and ultrasonically dispersed for 30 minutes. 1 g of 3-aminopropyltriethoxysilane was added and reacted at 110 °C under reflux for 12 hours. After the reaction was completed, the precipitate was centrifuged and washed three times each with toluene and anhydrous ethanol. The precipitate was then vacuum dried at 60 °C for 12 hours to obtain aminated halloysite nanotubes.
[0027] 0.2 g of aminated halloysite nanotubes were dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain a dispersion with a concentration of 0.2%. This dispersion was applied to the upper surface of the SPEEK porous support layer obtained in step (1) by vacuum filtration at a vacuum degree of -0.085 MPa for 15 minutes, allowing the aminated halloysite nanotubes to deposit on the surface of the support layer to form a continuous intermediate layer. After filtration, the membrane was dried in a 40°C drying oven for 6 hours to obtain a composite membrane loaded with an aminated halloysite nanotube intermediate layer.
[0028] (3) Dissolve 2,2′-bis(trifluoromethyl)-4,4′-diaminobiphenyl in deionized water to prepare an aqueous solution with a concentration of 2.0%, and add triethylamine as an acid acceptor. The amount of triethylamine added is 0.5% of the total mass of the aqueous solution. Lay the composite membrane obtained in step (2) flat, pour the above aqueous solution onto the upper surface of the aminated halloysite nanotube intermediate layer of the composite membrane to completely wet it, soak it for 5 minutes, then tilt it to drain, and roll it once along the membrane surface with a rubber roller to remove excess liquid until the membrane surface is wet and there are no flowing droplets. Then pour a hexane solution containing 0.15% trimesoyl chloride onto the same surface and carry out an interfacial polymerization reaction at 25°C for 2 minutes. After the reaction is completed, pour off the organic phase solution, place the composite membrane in an oven at 80°C for heat treatment for 10 minutes to obtain a fluorinated polyamide separation layer.
[0029] The resulting composite membrane was washed three times with deionized water to remove unreacted monomers and residual organic solvents, and then dried at 60°C to obtain the nanofiltration membrane used for high-temperature liquid-feed separation. Example 2
[0030] This embodiment provides a nanofiltration membrane for high-temperature liquid-feed separation, the preparation method of which includes the following steps: (1) Dissolve 10g of polyetheretherketone powder in 200mL of 98% concentrated sulfuric acid and stir at 78℃ for 10 hours. After the reaction is complete, slowly pour the product into a large amount of deionized water to precipitate it. Wash repeatedly with deionized water until the washing solution is neutral. Dry under vacuum at 60℃ for 24 hours to obtain sulfonated polyetheretherketone. The degree of sulfonation of the obtained sulfonated polyetheretherketone was determined to be 62% by acid-base titration.
[0031] 16g of the above-mentioned sulfonated polyetheretherketone was dissolved in 84g of N,N-dimethylformamide and stirred at 60°C for 12 hours. After standing to remove bubbles, a film-forming solution with a solid content of 16% was obtained. The film-forming solution was uniformly coated onto the upper surface of polyethylene terephthalate nonwoven fabric using a doctor blade with a doctor blade gap of 150μm. Immediately after coating, the nonwoven fabric and the coating layer were immersed in deionized water at 35°C for phase inversion molding for 10 minutes. After removal, the fabric was thoroughly washed with deionized water to obtain a porous support layer of sulfonated polyetheretherketone composited on the nonwoven fabric.
[0032] (2) 5 g halloysite nanotubes were dispersed in 150 mL of anhydrous ethanol and ultrasonically dispersed for 30 minutes. 1.75 g of 3-aminopropyltrimethoxysilane was added and reacted at 78 °C under reflux for 18 hours. After the reaction was completed, the precipitate was separated by centrifugation, and the precipitate was washed three times each with anhydrous ethanol and deionized water, and dried under vacuum at 60 °C for 12 hours to obtain aminated halloysite nanotubes.
[0033] 0.08 g of the above-mentioned aminated halloysite nanotubes were dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain a dispersion with a concentration of 0.08%. This dispersion was then applied to the upper surface of the sulfonated polyether ether ketone porous support layer obtained in step (1) by vacuum filtration at a vacuum degree of -0.085 MPa for 15 minutes, allowing the aminated halloysite nanotubes to deposit on the support layer surface to form a continuous intermediate layer. After filtration, the membrane was dried in a 40°C drying oven for 6 hours to obtain a composite membrane loaded with an aminated halloysite nanotube intermediate layer.
[0034] (3) Dissolve 4,4′-(hexafluoroisopropylidene)diphenylamine in deionized water to prepare an aqueous solution with a concentration of 2.8%, and add sodium hydroxide as an acid acceptor. The amount of sodium hydroxide added is 0.3% of the total mass of the aqueous solution. Lay the composite membrane obtained in step (2) flat, pour the above aqueous solution onto the upper surface of the aminated halloysite nanotube intermediate layer of the composite membrane to completely wet it, soak it for 5 minutes, then tilt it to drain, and roll it once along the membrane surface with a rubber roller to remove excess liquid until the membrane surface is wet and there are no flowing droplets. Then pour a cyclohexane solution containing 0.25% terephthaloyl chloride onto the same surface and carry out an interfacial polymerization reaction at 40°C for 4 minutes. After the reaction is completed, pour off the organic phase solution, place the composite membrane in a 70°C oven for heat treatment for 15 minutes to obtain a fluorinated polyamide separation layer.
[0035] The resulting composite membrane was washed three times with deionized water to remove unreacted monomers and residual organic solvents, and then dried at 60°C to obtain the nanofiltration membrane used for high-temperature liquid-feed separation. Example 3
[0036] This embodiment provides a nanofiltration membrane for high-temperature liquid-feed separation, the preparation method of which includes the following steps: (1) Dissolve 10g of polyetheretherketone powder in 200mL of 98% concentrated sulfuric acid and stir at 60℃ for 5 hours. After the reaction is complete, slowly pour the product into a large amount of deionized water to precipitate it. Wash repeatedly with deionized water until the washing solution is neutral. Dry under vacuum at 60℃ for 24 hours to obtain sulfonated polyetheretherketone. The degree of sulfonation of the obtained sulfonated polyetheretherketone was determined to be 48% by acid-base titration.
[0037] 19g of the above-mentioned sulfonated polyetheretherketone was dissolved in 81g of N-methylpyrrolidone and stirred at 60°C for 12 hours. After standing to remove bubbles, a film-forming solution with a solid content of 19% was obtained. The film-forming solution was uniformly coated onto the upper surface of a polypropylene nonwoven fabric using a doctor blade with a gap of 150μm. Immediately after coating, the nonwoven fabric and the coating layer were immersed in deionized water at 50°C for phase inversion molding for 10 minutes. After removal, the fabric was thoroughly washed with deionized water to obtain a porous support layer of sulfonated polyetheretherketone composited on the nonwoven fabric.
[0038] (2) 5 g halloysite nanotubes were dispersed in 150 mL of N,N-dimethylformamide and ultrasonically dispersed for 30 minutes. 0.6 g of 3-aminopropyltriethoxysilane was added, and the mixture was refluxed at 153 °C for 8 hours. After the reaction was completed, the mixture was centrifuged, and the precipitate was washed three times each with N,N-dimethylformamide and anhydrous ethanol, and then vacuum dried at 60 °C for 12 hours to obtain aminated halloysite nanotubes.
[0039] 0.4 g of the above-mentioned aminated halloysite nanotubes were dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain a dispersion with a concentration of 0.4%. This dispersion was then applied to the upper surface of the sulfonated polyether ether ketone porous support layer obtained in step (1) by vacuum filtration at a vacuum degree of -0.085 MPa for 15 minutes, allowing the aminated halloysite nanotubes to deposit on the support layer surface to form a continuous intermediate layer. After filtration, the membrane was dried in a 40°C drying oven for 6 hours to obtain a composite membrane loaded with an aminated halloysite nanotube intermediate layer.
[0040] (3) Dissolve 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene in deionized water to prepare an aqueous solution with a concentration of 1.5%, and add sodium carbonate as an acid acceptor. The amount of sodium carbonate added is 0.8% of the total mass of the aqueous solution. Lay the composite membrane obtained in step (2) flat, pour the above aqueous solution onto the upper surface of the aminated halloysite nanotube intermediate layer of the composite membrane to completely wet it, soak it for 5 minutes, then tilt it to drain, and roll it once along the membrane surface with a rubber roller to remove excess liquid until the membrane surface is wet and there are no flowing droplets. Then pour the Isopar G solution containing 0.12% isophthaloyl chloride onto the same surface and carry out the interfacial polymerization reaction at 50°C for 1.5 minutes. After the reaction is completed, pour off the organic phase solution, place the composite membrane in a 95°C oven for heat treatment for 5 minutes to obtain the fluorinated polyamide separation layer.
[0041] The resulting composite membrane was washed three times with deionized water to remove unreacted monomers and residual organic solvents, and then dried at 60°C to obtain the nanofiltration membrane used for high-temperature liquid-feed separation.
[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that it does not contain an aminated halloysite nanotube intermediate layer.
[0043] Specifically, after step (1) is completed, step (2) is not performed. Instead, the aqueous solution is poured onto the surface of the SPEEK porous support layer to carry out the interfacial polymerization reaction, following the method of step (3) in Example 1. The remaining steps and parameters are the same as in Example 1.
[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that the intermediate layer of aminated halloysite nanotubes is replaced with a mesoporous silica intermediate layer.
[0045] Specifically as follows: The sulfonated polyether ether ketone porous support layer was prepared according to step (1) of Example 1.
[0046] (2) 0.2 g of mesoporous silica nanoparticles were dispersed in 100 mL of deionized water and ultrasonically dispersed for 30 minutes to obtain a dispersion with a concentration of 0.2%. This dispersion was applied to the upper surface of the SPEEK porous support layer obtained in step (1) by vacuum filtration at a vacuum degree of -0.085 MPa for 15 minutes, so that the mesoporous silica nanoparticles were deposited on the surface of the support layer to form a continuous intermediate layer. After filtration, the membrane was dried in a 40°C drying oven for 6 hours to obtain a composite membrane loaded with a mesoporous silica intermediate layer.
[0047] Step (3) is the same as in Example 1.
[0048] Comparative Example 3 The difference between this comparative example and Example 1 is that the sulfonated polyether ether ketone porous support layer is replaced with a polyimide porous support layer.
[0049] Specifically as follows: (1) Dissolve 15g of soluble polyimide (Matrimid 5218) in 85g of N,N-dimethylacetamide and stir at 60℃ for 12 hours. After standing and degassing, a film-forming solution with a solid content of 15% is obtained. The film-forming solution is uniformly coated onto the upper surface of polyethylene terephthalate nonwoven fabric using a doctor blade with a doctor blade gap of 150μm. Immediately after coating, the nonwoven fabric and the coating layer are immersed in deionized water at 25℃ for phase inversion molding for 10 minutes. After removal, the nonwoven fabric is thoroughly washed with deionized water to obtain a polyimide porous support layer composited on the nonwoven fabric.
[0050] Steps (2)-(3) are the same as in Example 1.
[0051] Comparative Example 4 The difference between this comparative example and Example 1 is that the fluorinated polyamide separation layer is replaced with a m-phenylenediamine-trimethylammonium chloride polyamide separation layer.
[0052] Specifically as follows: A composite film loaded with an aminated halloysite nanotube intermediate layer was prepared according to steps (1)-(2) of Example 1.
[0053] Step (3) involves dissolving m-phenylenediamine in deionized water to prepare a 2.0% aqueous solution. The composite membrane obtained in step (2) is laid flat, and the aqueous solution is poured onto the upper surface of the aminated halloysite nanotube intermediate layer of the composite membrane to completely wet it. After soaking for 5 minutes, it is tilted and allowed to drain. A rubber roller is used to roll the membrane surface once in one direction to remove excess liquid until the membrane surface is wetted and free of flowing droplets. Then, a hexane solution containing 0.15% trimesoyl chloride is poured onto the same surface, and interfacial polymerization is carried out at 25°C for 2 minutes. After the reaction is complete, the organic phase solution is discarded, and the composite membrane is heat-treated in an 80°C oven for 10 minutes to obtain the m-phenylenediamine-trimethylammonium chloride polyamide separation layer.
[0054] The resulting composite membrane was washed three times with deionized water to remove unreacted monomers and residual organic solvents, and then dried at 60°C to obtain a nanofiltration membrane.
[0055] Performance testing I. Test Sample Take three nanofiltration membrane samples each from Examples 1-3 and Comparative Examples 1-4, and measure them under the same test conditions. The average value of the results is taken.
[0056] II. Test Items and Methods 1. Water flux The tests were conducted according to GB / T 34242-2017 "Test Methods for Nanofiltration Membranes". The test temperatures were 25℃ and 95℃, the operating pressure was 0.6 MPa, the cross-flow circulation rate was 1.2 L / min, and the effective membrane area was 20 cm². 2 Before testing, the test solution is preheated to the target temperature and then introduced into the cross-flow flat sheet membrane test cell. It is then pre-pressurized at the corresponding test temperature for 30 minutes until the flux stabilizes. After the flux stabilizes, the permeate volume is collected over a certain period using a graduated cylinder and stopwatch, and the water flux is calculated according to the formula.
[0057] 2. Sodium sulfate rejection rate The measurements were performed according to GB / T 34242-2017. The test temperatures were 25℃ and 95℃, the operating pressure was 0.6 MPa, the cross-flow circulation rate was 1.2 L / min, and the effective membrane area was 20 cm². 2 The feed solution was a 1000 mg / L Na₂SO₄ aqueous solution. Before testing, the test solution was preheated to the target temperature and then introduced into the cross-flow flat sheet membrane test cell. It was pre-pressurized for 30 minutes at the corresponding test temperature. The conductivity of the feed solution and permeate was measured using a conductivity meter (a conductivity-concentration standard curve was calibrated using a standard Na₂SO₄ solution before testing), and the rejection rate was calculated according to the formula.
[0058] 3. High-temperature flux change rate Calculated based on water flux test results at 25℃ and 95℃: High-temperature flux change rate = (J 95℃ -J 25℃ ) / J 25℃ ×100% 4. Pure water flux decline rate after long-term operation at high temperature The membrane was continuously operated for 100 hours at 95℃ and 0.6MPa, using a 1000mg / L Na₂SO₄ aqueous solution as the feed solution. After the operation, the membrane sample was removed and allowed to recover to 25℃. The pure water flux at 25℃ was then measured using the method described above and denoted as J. 25℃末 Calculate according to the formula: Pure water flux decay rate after long-term operation at high temperature = (J) 25℃ - J 25℃末 ) / J 25℃ × 100% 5. Changes in retention rate after long-term operation at high temperatures Under conditions of 95℃ and 0.6MPa, using a 1000mg / L Na₂SO₄ aqueous solution as the feed liquid, the system was continuously operated for 100 hours. The sodium sulfate rejection rate was measured before operation (initial at 95℃) and after operation (final at 95℃), and the difference was calculated. Change in retention rate after long-term operation at high temperature = R 95℃末 - R95℃初 Positive values indicate an increased rejection rate, while negative values indicate a decreased rejection rate.
[0059] The test results are shown in Table 1.
[0060]
[0061] As can be seen from the above performance test results, Examples 1 to 3 all performed excellently in all performance indicators. After running continuously for 100 hours in a high-temperature saline solution at 95°C, the pure water flux decay rate of the examples was very low and the rejection rate decreased by very little. This indicates that the membrane structure remained intact during long-term operation at high temperature, which fully verifies that the nanofiltration membrane of the present invention can effectively inhibit high-temperature structural damage.
[0062] In Comparative Example 1, due to the removal of the aminated halloysite nanotube interlayer, the fluorinated polyamide separation layer directly contacts the SPEEK support layer. At high temperatures, the lack of chemical bonding and hydrogen bonding between the separation layer and the support layer results in insufficient interfacial adhesion, leading to a significant decrease in retention rate and a marked decrease in flux after 100 hours of high-temperature operation. In Comparative Example 2, replacing the halloysite nanotubes with mesoporous silica, while the physical isolation effect of the interlayer remains, the silica surface lacks the hollow tubular structure characteristic of halloysite and the ability to form a dense hydrogen bond network between natural silanol groups and SPEEK sulfonic acid groups. This results in significantly insufficient interlayer adhesion, and the performance degradation after high-temperature operation is significantly higher than in the example. In Comparative Example 3, replacing the SPEEK support layer with polyimide, although PI itself has excellent heat resistance, its molecular chain lacks sulfonic acid groups, preventing sufficient hydrogen bonding interaction with the silanol groups on the halloysite nanotube surface. This leads to a lack of effective interfacial adhesion between the support layer and the interlayer at high temperatures, severe thermal expansion mismatch, and significant performance degradation after long-term operation. In Comparative Example 4, after the fluorinated polyamide separation layer was replaced, the lack of a rigid skeleton of biphenyl structure led to increased thermal motion of polymer chain segments at high temperatures. The free volume pores of the separation layer expanded significantly with increasing temperature, resulting in a significant deterioration in retention performance at high temperatures. After long-term operation, the performance degradation also increased significantly.
[0063] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A nanofiltration membrane for high-temperature liquid-feed separation, wherein the nanofiltration membrane has a four-layer composite structure, characterized in that, From bottom to top, they include: Non-woven fabric reinforcement layer; A sulfonated polyether ether ketone porous support layer is disposed on the upper surface of the nonwoven reinforcement layer; An aminated halloysite nanotube intermediate layer is disposed on the upper surface of the sulfonated polyether ether ketone porous support layer; A fluorinated polyamide separation layer is disposed on the upper surface of the intermediate layer of the aminated halloysite nanotubes. The fluorinated polyamide separation layer is formed by interfacial polymerization of a fluorinated aromatic diamine monomer and a polyacryl chloride monomer. The fluorinated aromatic diamine monomer is at least one of 2,2′-bis(trifluoromethyl)-4,4′-diaminobiphenyl, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, or 4,4′-(hexafluoroisopropylidene)diphenylamine.
2. The nanofiltration membrane for high-temperature liquid-feed separation according to claim 1, characterized in that, The nonwoven reinforcement layer is made of polyethylene terephthalate nonwoven fabric or polypropylene nonwoven fabric.
3. The nanofiltration membrane for high-temperature liquid-feed separation according to claim 1, characterized in that, The degree of sulfonation of the sulfonated polyether ether ketone is 45% to 65%.
4. The nanofiltration membrane for high-temperature liquid-feed separation according to claim 1, characterized in that, The preparation method of the sulfonated polyether ether ketone includes: dissolving polyether ether ketone in concentrated sulfuric acid, reacting at a temperature of 50-80°C for 4-12 hours, washing the reaction product with deionized water until neutral, and then drying it to obtain sulfonated polyether ether ketone.
5. The nanofiltration membrane for high-temperature liquid-feed separation according to claim 1, characterized in that, The preparation method of the aminated halloysite nanotubes includes: dispersing halloysite nanotubes in an organic solvent, adding a silane coupling agent, reacting at reflux temperature for 6 to 24 hours, and obtaining aminated halloysite nanotubes after washing and drying the reaction product. The silane coupling agent is 3-aminopropyltriethoxysilane or 3-aminopropyltrimethoxysilane.
6. The nanofiltration membrane for high-temperature liquid-feed separation according to claim 5, characterized in that, The mass ratio of halloysite nanotubes to silane coupling agent is 1:0.05 to 0.5; the organic solvent is selected from at least one of toluene, anhydrous ethanol, isopropanol or N,N-dimethylformamide.
7. The nanofiltration membrane for high-temperature liquid-feed separation according to claim 1, characterized in that, The polyacryl chloride monomer is at least one of pyromellitic trichloroisocyanurate, terephthaloyl chloride, or isophthaloyl chloride.
8. The method for preparing the nanofiltration membrane for high-temperature liquid-feed separation according to any one of claims 1-7, characterized in that, Includes the following steps: (1) Dissolve sulfonated polyether ether ketone in an organic solvent to prepare a film-forming solution, coat the film-forming solution on the surface of the nonwoven fabric reinforcement layer, and then immerse it in water for phase inversion to obtain a sulfonated polyether ether ketone porous support layer composite on the nonwoven fabric reinforcement layer. (2) Aminated halloysite nanotubes are dispersed in a liquid medium to form a dispersion, and the dispersion is coated on the surface of the sulfonated polyether ether ketone porous support layer. After drying, an aminated halloysite nanotube intermediate layer is formed. (3) An aqueous solution containing a fluorinated aromatic diamine monomer is applied to the surface of the intermediate layer of aminated halloysite nanotubes. After removing excess liquid from the surface, an organic solution containing a polyacrylamide monomer is applied to the same surface for interfacial polymerization. After the reaction is completed, the solution is heated to obtain a fluorinated polyamide separation layer, which is a nanofiltration membrane for high-temperature liquid-feed separation.
9. The preparation method according to claim 8, characterized in that, In step (1), the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; the mass concentration of sulfonated polyether ether ketone in the film-forming solution is 15% to 20%; and the temperature of the water used for the phase inversion is 25 to 60°C.
10. The preparation method according to claim 8, characterized in that, In step (2), the liquid medium is water or a mixture of ethanol and water; the mass concentration of aminated halloysite nanotubes in the dispersion is 0.05% to 0.5%; in step (3), the mass concentration of fluorinated aromatic diamine monomer in the aqueous phase solution is 1.0% to 3.0%; the mass concentration of polyacrylamide chloride monomer in the organic phase solution is 0.1% to 0.3%; the temperature of the interfacial polymerization reaction is 25 to 60°C, and the time is 1 to 5 minutes.
Citation Information
Patent Citations
Cross-linked fluorine-containing polyamide composite solvent resistance nano-filtration membrane, preparation method and application of membrane
CN109351190A
